Modeling and simulation of a stand-alone wind turbine supplying an inductive load through a long cable - Zakaria Al-Omari; Walid Emar (Institute of Advanced Engineering and Science, 2022)
This paper considers the principles of modeling, control, and simulation of variable speed wind turbines (VSWTs), based on a stand-alone doubly fed induction generator (DFIG). The DFIG is used to feed a three-phase highly inductive load through a long cable via a three-phase multi-level frequency converter (MLFC). The proposed MLFC increases the number of voltage levels with less power electronic components as compared to the conventional back-to-back AC/DC/AC converter. The length of the cable (transmission line TL) influences a mismatch between the load and TL impedances; therefore, a reflected signal will occur. If the